Disorder induced violet/blue luminescence in rf‐deposited ZnO films. Issue 4 (11th March 2013) - Peres, M.; Magalhães, S.; Soares, M. R.; Soares, M. J.; Rino, L.; Alves, E.; Lorenz, K.; Correia, M. R.; Lourenço, A. C.; Monteiro, T.
Abstract In this work ZnO thin films were deposited on different substrates, glass, silicon (100), and MgO (100) using rf‐magnetron sputtering at low temperature in order to promote a large defect density, aiming to study a possible correlation with the observed violet/blue emission band. The peak position, width and low energy band shape asymmetry of the violet/blue band was found to be dependent on the deposition temperature and oxygen partial pressure. The structural analysis of deposited films reveals an epitaxial relationship for the a ‐oriented ZnO/MgO while for the c ‐oriented ZnO/Si no epitaxial relation was found with the substrate. The dependence of the violet/blue band on temperature displays always a shift of the peak position to lower energies, discarding the hypothesis of a free to bound transition. The sublinear dependence of the emission intensity with the excitation intensity suggests that the violet/blue bands on both samples could have a donor‐acceptor pair nature. However, the unusually strong shift of the peak position to lower energies for the ZnO/MgO films and the emphasised asymmetric band shape for the ZnO/Si samples suggest that potential fluctuations in the electronic bands, due to disorder induced charged defects, could also be considered as an alternative recombination model for the violet/blue band. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)